Knowledge brokering: “Not a place for novices or new conscripts” - Cooper, Amanda; Rodway, Joelle; MacGregor, Stephen; Shewchuk, Samantha; Searle, Michelle (The Role of Knowledge Brokers in Education, 2019)
Growing interest in evidence-based policy and practice globally has led to the exploration of research brokering and networks as powerful mechanisms for knowledge mobilization (efforts to integrate research evidence into large scale K-12 education systems to improve outcomes in schools). Our chapter draws on data sources from projects conducted by the Research Informing Policy, Practice and Leadership in Education (RIPPLE) from Queen’s University. This chapter begins by conceptualizing knowledge mobilization in relation to four domains: research production, research use, research brokering, and research impact. Next, we outline core competencies for knowledge mobilization across three domains: knowledge, skills, and attitudes. Third, we provide a typology of research brokering organizations differentiated by funding sources and position within education system, and highlight eight brokering functions—increasing linkages and partnerships, awareness, accessibility, engagement, organizational development, implementation support, capacity building, and policy influence. Finally, we explore three evaluation frameworks to measure research brokering and partnerships, highlighting social network analysis as a powerful methodology to explore KMb networks in education.